A comprehensive review of the cosmeceutical benefits of Vanda species (Orchidaceae) - Ab. Hadi, Hazrina; Said Razal, Syarifah Nazira; Awadh, Ammar Ihsan JawaD (Natural Product, Inc., 2015)
Orchidaceae is the largest family of flowering plants with over 35,000 species and 850 genera. About 3300 species of orchids are found in Malaysia and the diversity is highest in the Main, Keledang, Bintang and Tahan Ranges. Apart from being prized for their beauty, orchids have long been used by humans for medicinal purposes. Today the uses of orchids have been expanded to the food and cosmetics industries. Many cosmeceutical companies use orchid extracts as an active ingredient in their products. Previous studies provide riveting insights into the potential uses of orchid extracts as an active agent in cosmetics. This paper describes the cosmeceutical potential of orchids as an anti-aging, and skin moisturizing agent. Orchid extracts from Vanda coerulea and V. teres delay aging caused by reactive oxygen species (ROS) following LV irradiation through their antioxidant and anti-inflammatory activity. These extracts also show anti-aging properties by stimulating cytochrome c oxidase (complex IV), which is part of the electron transport chain in mitochondria. Stimulation of cytochrome c oxidase improves the respiratory function of mitochondria in keratinocytes. The presence of mucilage in orchids enables them to maintain skin hydration. Mucilage functions as a moisturizer and emollient due to its high water binding capacity. Additionally, orchid extracts provide skin hydration by stimulating aquaporin 3 (AQP3) and LEKTI protein expression. The presence of AQP3 leads to a five-fold increase in water permeability, which subsequently increases stratum corneum hydration. Increased LEKTI protein expression mediated by orchid extracts reduces the degradation of desmoglein-1 and enhances the structural function of desmosomes, which play important roles in preventing water evaporation.